Allocation of parental care by Western Canada Geese Branta canadensis moffitti - Griggs, Kenneth M.; Black, Jeffrey M. (Wildfowl, 2017)
The level of parental care provided by Western Canada Geese Branta canadensis moffitti to their goslings (4â€“11 months of age) was measured in a resident population by determining proximity of goslings to the nearest parent, goslingsâ€™ daily attendance in the family unit, and the duration of the parent-gosling association during the first winter. Time spent in vigilance postures (watching for competitors and predators) and aggression (to maintain space for foraging within flocks) was determined for each family member. Male goslings were more â€œhelpfulâ€ in that they were more vigilant and aggressive than female goslings. Perhaps as a result, male goslings benefited more from all three measures of parental care than female goslings. Male goslings were on average closer to parents, in attendance more often, and had a longer duration of parent-gosling association during the first winter than their female siblings. Among females in the same brood (i.e. siblings), the most vigilant and aggressive were allocated more care as measured by proximity to parents, daily attendance, and duration of association with parents. Among male siblings, the most vigilant individuals were allocated with more care in terms of proximity to parents than less vigilant male goslings. Within sexes, gosling structural size (i.e. skull length) did not affect the allocation of parental care. With regard to parents, the level of female vigilance and aggression towards flock members was negatively correlated with the amount of â€œhelpâ€ provided by the most â€œhelpfulâ€ gosling in the brood, in terms of the goslingsâ€™ contribution to the family through their vigilance and aggressive behaviours. This finding suggests that female parents benefit from maintaining contact with â€œhelpfulâ€ goslings, more so than females with less â€œhelpfulâ€ goslings. This relationship was not apparent for male parents. The most interesting finding from this study was that parent geese appeared to base parental investment decisions more on their goslingsâ€™ behaviour rather than structural size. The energetic costs that mature goslings bear from assisting parents with family duties of watching for competitors and predators and defending foraging space within flocks may be compensated by longer-term benefits of prolonged association with their parents.